Omo sanza lettere? : The Relationship between Painting and Poetry in Leonardo da Vinco - Brigante Rovida, Anna Maria (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This essay intends to show that though it is necessary to consult Leonardo´s critique of poetry in order to understand the relationship between the so-called twin arts, it isn´t enough. It is essential to consider the various ways in which the Italian artist expresses himself showing that poetry and painting aren´t antagonistic per se but complementary, even more, the articulation between image and word is intimate and necessary for the understanding of the creative and cognitive intentions of the artist. Because of it the question: Leonardo omo sanza lettere?
Keywords: Leonardo da Vinci; poetry; painting; ut pictura poesis; ekphrasis